Aplikasi Monitoring Tamu Pada Sistem Keamanan Perumahan Komplek Berbasis Android - Wardani, Lidona Kusuma; Endri, Jon; Lindawati, L (STIKOM Tunas Bangsa Pematangsiantar, 2021)
There are so many cases that occur at home when the house is empty or being abandoned by its occupants, the impact of the theft is very detrimental to victims who have broken into their homes, these incidents often occur by damaging or breaking into the lock system on the doors and windows of the house. This theft causes unrest in the community because they feel less calm, safe, and comfortable when outside the home. In this study, an application was designed to make it easier to control the house with the use of IoT in creating an android-based information system that was applied to assist security guards in monitoring guests in real time. In this study, the information system used is facial recognition, where if there is a face that is not recognized or dangerous, the system will send a face image to the security guard android smartphone application.